Subthreshold operation of MOIS devices: Boundary of operation - Parnklang, Jirawath; Jindajitawat, Phumin; Titiroongruang, Wisut (My University, 2000)
The boundary of MOIS operating in subthreshold are presented on this article. The MOS transistor-like structure is MOIS (Complementary Metal Oxide Intrinsic-like Semiconductor, MOIS), which prepared on gold-doped silicon. In this condition causes to change many essential characteristics of the device. We demonstrate the analytical parameters and the experimental result of the device which use to determine the subthreshold regime.